2007
DOI: 10.1038/ng2078
|View full text |Cite
|
Sign up to set email alerts
|

Germline gain-of-function mutations in RAF1 cause Noonan syndrome

Abstract: Noonan syndrome is characterized by short stature, facial dysmorphia and a wide spectrum of congenital heart defects. Mutations of PTPN11, KRAS and SOS1 in the RAS-MAPK pathway cause approximately 60% of cases of Noonan syndrome. However, the gene(s) responsible for the remainder are unknown. We have identified five different mutations in RAF1 in ten individuals with Noonan syndrome; those with any of four mutations causing changes in the CR2 domain of RAF1 had hypertrophic cardiomyopathy (HCM), whereas affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
362
0
13

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 453 publications
(395 citation statements)
references
References 28 publications
13
362
0
13
Order By: Relevance
“…Infants with Costello syndrome are less likely to have severe pulmonary stenosis, or pulmonary stenosis with an atrial septal defect. The lack of complex CHDs currently distinguishes Costello syndrome from Noonan syndrome (PTPN11, RAF1) (and rarely, NF1) in which tetralogy of Fallot or atrioventricular septal defect have been reported occasionally [Lin et al, 2000;Sarkozy et al, 2003;Pandit et al, 2007;Razzaque et al, 2007]. The predominance of valve dysplasia and paucity of cardiac malformation is consistent with the view that these are disorders of dysplasia, rather than malformation.…”
Section: Comparison To Other Rasopathiesmentioning
confidence: 79%
“…Infants with Costello syndrome are less likely to have severe pulmonary stenosis, or pulmonary stenosis with an atrial septal defect. The lack of complex CHDs currently distinguishes Costello syndrome from Noonan syndrome (PTPN11, RAF1) (and rarely, NF1) in which tetralogy of Fallot or atrioventricular septal defect have been reported occasionally [Lin et al, 2000;Sarkozy et al, 2003;Pandit et al, 2007;Razzaque et al, 2007]. The predominance of valve dysplasia and paucity of cardiac malformation is consistent with the view that these are disorders of dysplasia, rather than malformation.…”
Section: Comparison To Other Rasopathiesmentioning
confidence: 79%
“…It was reported that gain-of-function mutations in PTPN11 (encoded SHP2) 47,48 and RAF1 49,50 cause Noonan syndrome with hypertrophic cardiomyopathy, a genetic disorder in which the heart muscle becomes thick. In contrast, loss-of-function mutations of RAF1 in humans 51 or genetic deletion of SHP2 28,52 and Raf1 53 in mice cause DCM.…”
Section: Resultsmentioning
confidence: 99%
“…Mutations in SOS1 were identified in only 10% of our patients with NS and CFC syndrome. Presently unknown genetic causes for mutation-negative NS and related disorders, including recently identified mutations in RAF-1 Razzaque et al 2007), remain to be identified in molecules in the RAS/MAPK cascade.…”
Section: Discussionmentioning
confidence: 99%